Kecenderungan pengundi muda : Kajian kes negeri Perlis - Affendi, Rajini Kanth (2023)
GE has been one of the factors that contributes to the party’s winning percentage or determining factors. In this study, young voters refer to who are registered as voters and are between 21 and 40 years old. The government's latest decision to lower the voting age from 21 to 18 is a commendable initiative to increase the participation of youths in the formation of the government and the administration of the country. Through the increasing trend of modernization across the country, it has a direct impact on the increase in political literacy or the level of political literacy among the society, especially among young people. Problems that exist to influence the inclinations of young voters are such as the inclusive policies of the contesting parties, the characteristics of credible candidates highlighted by the contesting parties and current issues that affect the sensitivities of young voters such as corruption, employment opportunities and cost of living. This study uses qualitative methods through interviews and also focus group interviews. The findings of this study clearly show that the tendency of young voters in Perlis to take care of the party's policies and also the characteristics of the candidates who bring a good background in terms of personality, integrity and leadership experience. Local and national issues are also of concern to young voters in Perlis such as employment opportunities, cost of living and educational opportunities. The inclination of the youth in the selection of political leaders is an important aspect to be examined because it reflects the hopes of the youth towards the political leaders who will lead the country in the future.